Pathway correcting DNA replication errors in Saccharomyces cerevisiae. - Morrison, A (1993)
Mutation of predicted 3'-->5' exonuclease active site residues of Saccharomyces cerevisiae POL3 DNA polymerase (delta) or deletion of the PMS1 mismatch repair gene lead to relative (to wild type) spontaneous mutation rates of approximately 130 and 41, respectively, measured at a URA3 reporter gene inserted near to a defined replication origin. The POL3 exonuclease-deficient mutant pol3-01 generated most classes of single base mutation in URA3, indicating a broad specificity that generally corresponds to that of the PMS1 system. pol3-01 pms1 haploid cells ceased growth after a few divisions with no unique terminal cell morphology. A pol3-01/pol3-01 pms1/pms1 diploid was viable and displayed an estimated URA3 relative mutation rate of 2 x 10(4), which we calculate to be catastrophically high in a haploid. The relationship between the relative mutation rates of pol3-01 and pms1 was multiplicative, indicating action in series. The PMS1 transcript showed the same cell cycle periodicity as those of a set of DNA replication genes that includes POL3, suggesting PMS1 is co-regulated with these genes. We propose that the POL3 3'-->5' exonuclease and the PMS1 mismatch repair system act on a common pathway analogous to the dnaQ-->mutHLS pathway of DNA replication error correction in Escherichia coli.